MicroRNA29B induces fetal hemoglobin via inhibition of the HBG repressor protein MYB in vitro and in humanized sickle cell mice - Gu, Qingqing; Palani, Chithra D.; Smith, Alana; Li, Biaori; Amos-Abanyie, Ernestine Kubi; Ogu, Ugochi; Lu, Lu; Pace, Betty S.; Starlard-Davenport, Athena (Frontiers in Medicine, 2022)
Introduction Therapeutic strategies aimed at reactivating HBG gene transcription and fetal hemoglobin (HbF) synthesis remain the most effective strategy to ameliorate the clinical symptoms of sickle cell disease (SCD). We previously identified microRNA29B (MIR29B) as a novel HbF inducer via targeting enzymes involved in DNA methylation. We provided further evidence that the introduction of MIR29B into KU812 leukemia cells significantly reduced MYB protein expression. Therefore, the aim of this study was to determine the extent to which MIR29B mediates HbF induction via targeting MYB in KU812 leukemia cells and human primary erythroid progenitors and to investigate the role of MIR29B in HbF induction in vivo in the humanized Townes SCD mouse model. Materials and methods Human KU812 were cultured and normal CD34 cells (n = 3) were differentiated using a two-phase erythropoiesis culturing system and transfected with MIR29B (50 and 100 nM) mimic or Scrambled (Scr) control in vitro. A luciferase reporter plasmid overexpressing MYB was transfected into KU812 cells. Luciferase activity was quantified after 48 h. Gene expression was determined by quantitative real-time PCR. In vivo studies were conducted using Townes SCD mice (6 per group) treated with MIR29B (2, 3, and 4 mg/kg/day) or Scr control by 28-day continuous infusion using subcutaneous mini osmotic pumps. Blood samples were collected and processed for complete blood count (CBC) with differential and reticulocytes at weeks 0, 2, and 4. Flow cytometry was used to measure the percentage of HbF-positive cells. Results In silico analysis predicted complementary base-pairing between MIR29B and the 3′-untranslated region (UTR) of MYB. Overexpression of MIR29B significantly reduced MYB mRNA and protein expression in KU812 cells and erythroid progenitors. Using a luciferase reporter vector that contained the full-length MYB 3′-UTR, we observed a significant reduction in luciferase activity among KU812 cells that co-expressed MIR29B and the full-length MYB 3′-UTR as compared to cells that only expressed MYB 3′-UTR. We confirmed the inhibitory effect of a plasmid engineered to overexpress MYB on HBG activation and HbF induction in both KU812 cells and human primary erythroid progenitors. Co-expression of MIR29B and MYB in both cell types further demonstrated the inhibitory effect of MIR29B on MYB expression, resulting in HBG reactivation by real-time PCR, Western blot, and flow cytometry analysis. Finally, we confirmed the ability of MIR29B to reduce sickling and induce HbF by decreasing expression of MYB and DNMT3 gene expression in the humanized Townes sickle cell mouse model. Discussion Our findings support the ability of MIR29B to induce HbF in vivo in Townes sickle cell mice. This is the first study to provide evidence of the ability of MIR29B to modulate HBG transcription by MYB gene silencing in vivo. Our research highlights a novel MIR-based epigenetic approach to induce HbF supporting the discovery of new drugs to expand treatment options for SCD.